2019
DOI: 10.1161/jaha.118.009380
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Benefits From Supervised Treadmill Exercise in People With Peripheral Artery Disease

Abstract: Background It is currently unknown whether 6 months of supervised treadmill exercise has a durable benefit on 6‐minute walk performance, even after exercise is completed, in people with peripheral artery disease. Methods and Results A total of 156 participants with peripheral artery disease were randomized to 1 of 3 groups: supervised treadmill exercise, supervised resistance training, or attention control. Participants received supervised sessions during months 1 to 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
2
21
0
5
Order By: Relevance
“…The functional status of the patients was measured using the WIQ, which has been validated as a measure of perceived difficulty concerning walking distances and speeds and the ability to climb stairs [39]; significant improvements were seen in walking distance but benefits regarding walking speed and stair-climbing ability were not observed. These results are similar to those of other exercise intervention studies, which reported significant effects on WIQ walking distance and no effects on other outcome measures [40,41].…”
Section: Principal Findingssupporting
confidence: 89%
“…The functional status of the patients was measured using the WIQ, which has been validated as a measure of perceived difficulty concerning walking distances and speeds and the ability to climb stairs [39]; significant improvements were seen in walking distance but benefits regarding walking speed and stair-climbing ability were not observed. These results are similar to those of other exercise intervention studies, which reported significant effects on WIQ walking distance and no effects on other outcome measures [40,41].…”
Section: Principal Findingssupporting
confidence: 89%
“…In a randomised study, 156 participants were allocated to supervised treadmill exercise, supervised resistance training, or oral advice about nutrition and training. (35) After 6 months, the 6 minute walk distance improved only in the treadmill exercise group (36.1 m, 95% CI 13.9 -58.3), but at 12 months neither treadmill nor resistance significantly differed from baseline or control (walking distance: +7.5m and +6.1m).…”
Section: Proximal Aortic Longitudinal Strainmentioning
confidence: 86%
“…In addition to reducing the strength of the lower limb muscles [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], chronic lower limb ischemia also changes the gait pattern. Compared to a group of healthy individuals, people with PAD exhibit an extended stance phase while simultaneously shortening the swing phase [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary aims of physical rehabilitation are to extend the walking distance until claudication onset and to reduce pain, which can be achieved through regular physical training [ 12 ]. Treadmill training is the current gold standard for rehabilitation; however, researchers have observed a non-physiological gait pattern in people with PAD due to their fear of falling [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%